UPAYA MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI PECAHAN SEDERHANA MENGGUNAKAN MEDIA KONKRET PADA SISWA KELAS III DI UPT SDN 281 GRESIK - Suroso, Suroso; Dasrina, Dasrina (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2024)
In the pre-cycle formative test, the result of learning Mathematics for simple fractions showed a very low average score of 57.3 with a completeness percentage of 20%. This result is because students think mathematic is a difficult subject, so that students are less interested, low motivation and lack of understanding. Therefore, it is necessary to improve learning for class III students at UPT SDN 281 Gresik in mathematics lesson about simple fractions using concrete media, in this case concrete media use snacks. This research has the goal of increasing student learning outcomes. This research method is qualitative in the form of the Classroom Action Research. The subjects in this study were class III students at UPT SDN 281 Gresik, which consisted of 15 students consisting of 7 male students and 8 famale students. This research occurred in 2 cycles. Cycle 1 obtained increased results, with the average value of 64.7 with a completeness percentage of 47%. In cycle 2 there was a very significant increase, with the formative test score of 83 with a completeness percentage of 93%. This shows that the use of concrete media in mathematics lessons about simple fractions for class III UPT SDN 281 Gresik students can improve student learning outcomes. Keywords : Mathematics, Simple Fractions, Concrete Media.